CHILD MARRIAGE CONDITIONALITY AND ITS DISPENSATION IN MAHKAMAH SYAR’IYAH ACEH, INDONESIA - Raudhatul Jannah; M. Ya’kub Aiyub Kadir (Universitas Syiah Kuala, 2021)
This research aims to explain the policy regarding the conditionality and its dispensation of child marriage and to find out the effectiveness of the Law Number 16 Year 2019 Concerning the Amendment of Law Number 1 Year 1974 Concerning Marriage Law as well as the implementation of child marriage conditionality in Aceh by analysing Mahkamah Syar’iyah decisions. This research uses normative empirical legal research which mostly discusses on the Marriage Law and focuses on the norms regarding the conditionality and its dispensation of child marriage that is regulated under the Marriage Law and the implementation in Aceh. Keywords : Child Marriage, Children Rights, Legal problems, Mahkamah Syar’iyah.